Ihmāl And I'jām In Al-Jawharī’s Al-Ṣiḥāḥ: A Phonetic and Semantic Study/ ظاهرة الإهمال والإعجام في معجم الصَّحاح للجوهري: دراسة صوتية دلالية - Marwa Abdulkarim Jumaa; Osama Mohammed Suwailem (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study investigates Al-Jawharī’s treatment of ihmāl (undotting) and iʿjām (dotting) in his renowned dictionary Al-Ṣiḥāḥ, highlighting a linguistic phenomenon that has received little independent attention despite its significance in Arabic philology. By examining how the presence or absence of a single consonantal dot can alter meaning, the research explores the phonetic and semantic dimensions of Arabic lexicography. Using an analytical and comparative approach, the study analyzes lexical entries that exhibit variation in dotting, supported by evidence from Qur’anic readings, prophetic traditions, and classical poetry. It also compares Al-Jawharī’s handling of such variations with that of other major lexicographers to uncover his methodological principles in organizing and explaining dotted and undotted forms. The findings reveal that consonantal dotting not only influences meaning but also reflects the linguistic precision and awareness of early lexicographers. Moreover, the study demonstrates how phonetic features shape semantic distinctions and how Qur’anic citations contribute to reinforcing lexical meanings within Al-Ṣiḥāḥ.